Diagnosis of hyperprolactinemia in women: A Position Statement from the Brazilian Federation of Gynecology and Obstetrics Associations (Febrasgo) and the Brazilian Society of Endocrinology and Metabolism (SBEM) - Glezer, Andrea; Garmes, Heraldo Mendes; Kasuki, Leandro; Martins, Manoel; Elias, Paula Condé Lamparelli; Nogueira, Vania dos Santos Nunes [UNESP]; de Sá Rosa-E-Silva, Ana Carolina Japur; Maciel, Gustavo Arantes Rosa; Benetti-Pinto, Cristina Laguna; Nácul, Andrea Prestes (Archives of Endocrinology and Metabolism, 2024)
Hyperprolactinemia is a frequent cause of menstrual irregularity, galactorrhea, hypogonadism, and infertility. The most common etiologies of hyperprolactinemia can be classified as physiological, pharmacological, and pathological. Among pathological conditions, it is essential to distinguish prolactinomas from other tumors and pituitary lesions presenting with hyperprolactinemia due to pituitary stalk disconnection. Proper investigation considering clinical data, laboratory tests, and, if necessary, imaging evaluation, is important to identify the correct cause of hyperprolactinemia and manage the patient properly. This position statement by the Brazilian Federation of Gynecology and Obstetrics Associations (Febrasgo) and Brazilian Society of Endocrinology and Metabolism (SBEM) addresses the recommendations for measurement of serum prolactin levels and the investigations of symptomatic and asymptomatic hyperprolactinemia and medication-induced hyperprolactinemia in women.
Keywords: hook effect; hyperprolactinemia; macroprolactin; pituitary tumor; Prolactinoma